Two Techniques (Spectrophotometric and Turbidimetric) for Determination of Ciprofloxacin HCl in Pharmaceutical Drugs with Comparison between the Techniques - Hammood , Mohammad K.; Jeber, Jalal N.; Muhamad, Yasmeen H. (Iraqi Journal of Science, 2022)
A new, effective, simple and inexpensive method was developed for determination the amounts of Ciprofloxacin HCl in solutions and in tablets by spectrophotometry and turbidity using sodium tungstate as reagent. Also, in this paper comparison between two techniques was conducted. The reaction between the Ciprofloxacin HCl and reagent in acidic media formed a yellowish white complex. Chemical and physical conditions have been investigated. The Linear range for spectroscopic and turbidimetric techniques were (0.05-1.25) and (0.05-3.0) mmol.L-1 with correlation coefficients (0.9956) and (0.9941) respectively. The limits of detection were 7×10-5 and 5×10-5 mol.L-1. The proposed method is good alternative for determination of Ciprofloxacin HCl in tablets.